Gender stereotypes in advertising rhetoric in France and in Russia - A V Strachova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2010)
The article is devoted to the advertising rhetoric and techniques of verbal effects, which are based on gender stereotypes of Russian and French linguistic culture community.